DNA double helix promotes a linkage isomerization reaction in trans-diamminedichloroplatinum(II)-modified DNA. - Dalbiès, R (1994)
In the reaction between trans-diamminedichloroplatinum(II) and a single-stranded pyrimidin-rich oligodeoxyribonucleotide (22-mer) containing the central sequence TGAGT, the 1,3-trans-[Pt(NH3)2[d(GAG)]] cross-link is formed. The 1,3-intrastrand cross-link is inert within the single-stranded oligonucleotide. In contrast, it rearranges to an interstrand cross-link when the platinated oligonucleotide is paired with its complementary deoxyribo- or ribonucleotide strand. The half-life of the 1,3-intrastrand cross-link, approximately 6 h at 37 degrees C, is independent of the nature and concentration of the salt (NaCl or NaClO4). It is not dramatically affected when the intervening adenine residue between the chelated guanine residues is replaced by a cytosine or a thymine residue or when the T.A base pair adjacent to the 5' or 3' side of the adduct is replaced by a C.G base pair. On the other hand, a mismatch on the 3' or 5' side of the adduct prevents the rearrangement. We propose that the linkage isomerization reaction results from a direct nucleophilic attack of the cytosine residue complementary to the platinated 5' guanine residue on the platinum residue. Among others, the potential use of the DNA.RNA-promoted reaction is discussed in the context of the antisense strategy to irreversibly cross-link the antisense oligonucleotides to their targets.